Features of social activity of older persons (The Journal of Psychology and Sociology, 2017)
Changing social status of the person in old age, caused primarily the termination or limitation of employment, the transformation of values, of the lifestyle and communication, as well as the emergence of various difficulties in social and domestic, as well as in psychological adaptation to the new conditions, dictated by the need to develop and implementation of specific approaches, forms and methods of social work with the elderly. Changing social status of the person in old age, as practice shows, first of all a negative effect on the moral and material situation negatively affects the mental state reduces its resistance to disease and adaptation to environmental change. Values, status, role covers all aspects of human life, which creates a certain difficulty in determining the value orientation of personality structure, factors of its determination. The essence of aging through a description of the qualitative characteristics of the age, which include the processes of biological aging, changing social status of the elderly (change of status, role, lifestyle, etc.), psychological problems (number of older crises, personality changes, and others.). The analysis of the various points of view on the types of aging, resulting identified two generic types of aging: active aging (representatives of this type without any emotional disturbance experienced this period of life) and passive old age (the representatives of this type are experiencing a painful feeling of uselessness, narrowing the range of interests, alienation). The authors analyzed the most studied works and concluded that case, the period of aging creates a new value-normative concept of identity and raise issues related to the problems of older people to adapt to the changing conditions of their lives.
Keywords: elderly people; advanced age; gerontology; geriatrics; status; activity; social activity; therapy.